Modification and adsorption of triazine collectors of sperrylite (PtAs2), platarsite (PtAsS) and palladoarsenide (Pd2As) mineral surfaces - Nemutudi, Bradley (My University, 2025)
There are still difficulties in separating valuable minerals from gangue minerals, especially when it comes to extracting arsenides, or platinum group minerals (PGMs), like “sperrylite, platarsite and palladoarsenide, which are mostly found in the Platreef Bushveld Complex. According to reports, the flotation of PGMs resulted in low recovery when using traditional xanthates. This was owed to the report that the arsenides PGMs minerals are not easy to float, and therefore new collectors are required to enhance the recovery and separation of hard to float arsenide minerals. In minerals flotation, the pH effect is crucial in maximizing the recovery of PGMs. The study on the performance of and sodium hydroxide (NaOH) molecule and normal butyl xanthate (NBX), normal butyl dithiocarbamate (NBDTC) and the novel 2,6- dithio-4-butylamino-1,3,5-triazine (DTBAT) collectors onto sperrylite, platarsite and palladoarsenide mineral surfaces were performed using computational density functional theory with dispersion correction (DFT-D3) and experimental (microcalorimetry and microflotation) approaches. Experimentally, microcalorimetry and microflotation tests were conducted using pure synthesised sperrylite mineral. The collectors were adsorbed computationally on dry sperrylite, platarsite and palladoarsenide surfaces under neutral, alkaline and acidic conditions. Sodium hydroxide adsorption was also performed to determine the adsorption capacity with the sperrylite, platarsite and palladoarsenide (100) surfaces compared to the collector adsorptions. To compare the structural properties of each PtAs2, PtAsS and Pd2As structures, geometry optimisations were carried out. The bulk PtAs2 benefited from a hydrostatic pressure of 2.0 GPa, which resulted in lattice parameters of a = 5.967 Å and a band gap of 0.264 eV, which were in agreement with experiments. At 14.0 GPa, the lattice parameter a = 5.787 Å was determined for PtAsS, which agreed well with the experimental findings. For computational aspect, the PtAs2, PtAsS and Pd2As models were evaluated using the most stable surface plane of (100), which was found to give the lowest surface energy compared to the other surface planes. This was also complemented by the plotted X-ray diffraction (XRD), where the (200) plane for PtAs2 and PtAsS and the (300) plane for Pd2As, which are similar to the (100) plane/surface, were displayed the most dominant planes due to the highest intensity.” The computed surface energies for (100) PtAs2, PtAsS and Pd2As were 1.05 J/m2, 0.56 J/m2 and 1.46 J/m2, respectively. Several adsorption sites were considered in order to identify the most stable exothermic preferred site. “It was observed that the SNBX, SNBDTC and SDTBAT collectors preferred to adsorb on the surface Pt and As atoms through S atoms on sperrylite and platarsite, while on palladoarsenide they adsorbed on the 3-coordinated Pd atoms through S and N atoms.” For dry sperrylite surface under neutral and alkaline conditions the collectors preferred a Pt-bidentate (SNBX and SNBDTC) and Pt-tridentate (SDTBAT) adsorption modes. Under acidic conditions all the three collectors favoured a Pt-monodentate adsorption mode. The adsorption energies followed the decreasing order and therefore decreasing adsorption strength as: SDTBAT > SNBDTC > SNBX, indicating that the SDTBAT had strong exothermic adsorption at neutral conditions. In alkaline conditions, the SNBX gave the most exothermic adsorption energy and the trend followed the decreasing order as: SNBX > SNBDTC > SDTBAT. The HNBDTC gave strong adsorption energy under acidic condition and the order decreased as: HNBDTC > HDTBAT > HNBX. Microcalorimetry and microflotation techniques were used to supplement the adsorption of sperrylite mineral. It was noted that the neutral condition was in agreement with the microcalorimetry (pH = 7) heats of adsorption where SDTBAT exhibited stronger adsorption. The SNBX provided the best flotation performance when compared to the SNBDTC and SDTBAT collectors, according to the microflotation recoveries conducted under alkaline conditions (pH = 9). This was in agreement with the prediction of the computational simulation. The microflotation recoveries under acidic conditions (pH = 4) showed that the HNBDTC had higher recoveries than HNBX and HDTBAT, which compared well with computational-acidic adsorptions on dry sperrylite surface. “Therefore computational-acidic and microflotation deliver similar outcomes and it was depicted that sperrylite floats better under acidic conditions using dithiocarbamate collector with higher recoveries of 41.46%. The adsorption energies on dry platarsite surface under neutral conditions for SNBX and SDTBAT collectors preferred to adsorb in a Pt-monodentate adsorption mode between the collector S atoms on surface Pt atom. The SNBDTC was found to desorb from the surface. Under alkaline conditions, the adsorption of SNBX, SNBDTC and SDTBAT preferred to form in a Pt-monodentate bonding mode. The HNBDTC preferred a Pt-monodentate bonding mode, whereas the S and N atoms of HNBX and HDTBAT desorbed from the surface. It was found that in both neutral and acidic conditions, the adsorption energies followed the decreasing order as: DTBAT > NBDTC > NBX. This suggested that DTBAT had strong affinity with the surface and therefore demonstrated that it could be utilised preferably under neutral and acidic conditions giving better performance than the NBX and NBDTC collectors. The SNBX gave strong adsorption energy under alkaline conditions on dry platarsite (100) surface, and the trend followed as: SNBX > SNBDTC > SDTBAT. This indicated that the SNBX may have better performance in improving the flotation of platarsite mineral surface at alkaline conditions. For palladoarsenide mineral surface, the collectors were observed to favour a Pd-bidentate (NBX and NBDTC) and a Pd-tridentate (DTBAT) adsorption mode under neutral, alkaline and acidic conditions. “The adsorption energies showed that SDTBAT adsorbed stronger under neutral conditions and the adsorption trend followed the decreasing order as: SDTBAT > SNBDTC > SNBX. Most significantly, it was found that the SDTBAT had strong adsorption than the SNBX and SNBDTC, suggesting a potential substitute of SNBX and SNBDTC collectors under neutral conditions. Under alkaline conditions, the SNBX gave the most exothermic adsorption energies and the trend followed the decreasing order as: SNBX > SNBDTC > SDTBAT. According to these findings, SNBX is a highly effective collector that can enhance palladoarsenide mineral recovery in alkaline environment. Under acidic conditions, the collector adsorption energies decreased in the order: HNBDTC > HNBX > HDTBAT, and clearly the HNBDTC showed the strongest exothermic adsorption. It was apparent that the HNBDTC collector displayed an ability to improve the palladoarsenide mineral recovery in acidic condition.” A variety of arsenide minerals may benefit from the flotation collectors that are designed based on the adsorption of xanthate, DTC, and s-triazine as collectors on PtAs2, PtAsS, and Pd2As. It was evident that under various pH conditions, the collectors NBX, NBDTC and DTBAT showed the capacity to enhance the recovery of sperrylite, platarsite and palladoarsenide mineral surface. Sperrylite and palladoarsenide minerals would be best floated using s-triazine under neutral, xanthate under alkaline and DTC under acidic conditions, while platarsite would be floated using s-triazine under neutral and acidic conditions and xanthate under alkaline. This demonstrated that the xanthate, DTC and s-triazine had the ability to improve the recovery of sperrylite, platarsite and palladoarsenide under different pH conditions. Interestingly, it was noted that the adsorption were more exothermic on palladoarsenide compared to the platarsite and sperrylite mineral surface. This revealed how the minerals recovered in various ways during flotation. It is clear that palladoarsenide had good collector interactions compared to sperrylite and platarsite. These findings thus paved a way for design of novel collectors for sperrylite, platarsite, palladoarsenide and other various chalcogenide minerals in order to improve their recovery.
Thesis (Ph.D. (Physics)) -- University of Limpopo, 2025
Keywords: Sperrylite; Palladoarsenide; Platarsite; Mineral; Platinum group; Palladium; Heptazine; Arsenate minerals; Gallium arsenide